The Relevance of Public Governance to National Environmental Performance - Basrija, Andre; Handoyo, Sofik (Universitas Padjadjaran, 2019)
The study aims to examine the influence of public governance on national environmental performance. Public governance in this study consists of four attributes, namely government accountability, political stability, government effectiveness, and regulatory quality. This study was triggered by the phenomenon that countries with excellent economic performance, but they do not always have an excellent national environmental performance. The study involved 155 countries member of World Bank countries. This study adopted a Purposive Sampling technique. Path analysis was applied in this study because there is a correlation among independent variables. Public governance was measured using the Worldwide Governance Indicator (WGI) scores by the World Bank. Meanwhile, environmental performance was measured using the Environmental Performance Index (EPI) score by The Yale Center for Environmental Law & Policy (YCELP). Simultaneously, the result indicates that government accountability, political stability, government effectiveness, and regulatory quality have a significant influence on national environmental performance. However, partially, only government effectiveness variable has a significant influence on national environmental performance. Meanwhile, government accountability, political stability, and regulatory quality do not have a substantial effect on national environmental performance.